A Social‐Ecological Framework to Integrate Multiple Objectives for Environmental Flows Management. (April 2014) - Martin, David M.; Harrison‐Atlas, Dylan; Sutfin, Nicholas A.; Poff, N. LeRoy
Abstract "Environmental flows" is a research discipline that emphasizes freshwater allocation in rivers to sustain desired ecological conditions and human well‐being. The basis for environmental flow requirements has traditionally relied on hydrological and ecological data. Contemporary methods focus on detailed hydro‐ecological relationships within river ecosystems; however, there is currently no structured approach to systematically incorporate socially relevant data into the environmental flows discipline. To address this limitation we developed a flexible framework that applies a social‐ecological systems approach to account for multiple flow‐related objectives that reflect both biophysical sustainability and societal preferences. First, we conceptualize the freshwater social‐ecological system as a hierarchy of human and environmental domains. Then, we recommend stepwise procedures to assess flow‐related vulnerabilities of important system attributes, address their feedbacks, and translate these assessments to a common classification for comparative analyses that guide holistic flow management decisions.